Computation of large datasets - Tan, R.; Leong, J.; Sidhu, Amandeep (2018)
© Springer International Publishing AG 2018. With our solution, existing IT solutions of enterprises can be integrated with the cloud hence increasing the breadth of applications supported and improving performance with reduced additional overhead since additional storage and computing power become easily available on demand. This capability will be demonstrated by the prototype created at the end of the project.